Telenomus remus Nixon Egg Parasitization of Three Species of Spodoptera Under Different Temperatures - Pomari, A. F.; Bueno, A. F.; Bueno, Regiane Cristina Oliveira de Freitas [UNESP]; Menezes, A. O. (Springer Nature, 2013)
Telenomus remus Nixon is a promising biocontrol agent as an egg parasitoid of Spodoptera spp., but the lack of information on the host-parasitoid interactions in this system precludes its applied use in agriculture. Therefore, we studied the parasitism capacity of T. remus on eggs of Spodoptera cosmioides (Walker), Spodoptera eridania (Cramer), and Spodoptera frugiperda (Smith) in a range of temperatures (19, 22, 25, 28, 31, and 34 ± 1°C) under controlled conditions (70 ± 10% RH and 12 h photophase). Egg masses of Spodoptera spp. were offered to a single-mated T. remus female on a daily basis. More than 80% lifetime parasitism on eggs of S. cosmioides, S. frugiperda, and S. eridania was reached from 1 to 5, 1 to 7, and 1 to 9 days, respectively, at temperatures from 19 to 34°C. More than 80% parasitization was obtained at extreme temperatures for all hosts studied. Lifetime parasitization of S. frugiperda, S. cosmioides, and S. eridania was affected by temperature, with the lowest values for S. frugiperda (34°C) and S. cosmioides (19 and 34°C). Parasitization of S. eridania eggs was reduced around 18% at 28 and 31°C, but dropped more severely at 34°C. Parasitoid longevity was reduced as temperature increased. Thus, our data indicated that T. remus might be suitable as a biocontrol agent against S. eridania, S. cosmioides, and S. frugiperda in geographical areas that fit the temperature range studied here, even though T. remus parasitism was reduced at 34°C. © 2013 Sociedade Entomológica do Brasil.
Keywords: Biological control; egg parasitoid; fall armyworm; southern armyworm; velvet armyworm